2022
DOI: 10.3389/fpsyg.2022.960092
|View full text |Cite
|
Sign up to set email alerts
|

Specific relations of visual skills and executive functions in elite soccer players

Abstract: Visual and cognitive skills are key to successful functioning in highly demanding settings such as elite sports. However, their mutual influence and interdependencies are not sufficiently understood yet. This cross-sectional study examined the relationship between visual skills and executive functions in elite soccer players. Fifty-nine male elite soccer players (age: 18–34 years) performed tests assessing visual clarity (left-, right-, and both eyes), contrast sensitivity, near-far quickness, and hand-eye coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Correlations between the improvement of visual skills and certain subdomains of cognitive functions have been scarcely explored in the literature. Only Knöllner et al [ 98 ] investigated the connection between visual skills and executive functions and referred to the strongest correlation between visual skills and working memory function. Regarding time since stroke, the studies with the longest time since stroke showed negative and the lowest positive effects for visual processing speed [ 84 , 90 ] and negative effects for cognitive flexibility [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between the improvement of visual skills and certain subdomains of cognitive functions have been scarcely explored in the literature. Only Knöllner et al [ 98 ] investigated the connection between visual skills and executive functions and referred to the strongest correlation between visual skills and working memory function. Regarding time since stroke, the studies with the longest time since stroke showed negative and the lowest positive effects for visual processing speed [ 84 , 90 ] and negative effects for cognitive flexibility [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies from the pre-COVID-19 period on soccer players’ visual skills were categorized as “performance” ( Song et al, 2019 ; Bekris et al, 2020 ). However, during the COVID-19 pandemic, the Topic Area “Performance-Visual Skill” disappeared, and cognitive keywords that are important in visual-skill research emerged, which could be interpreted as a topic area in the field of psychology ( Casella et al, 2022 ; Knollner et al, 2022 ). Soccer players’ psychological state can be attributed to both self-influences and external/environmental factors ( Schinke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up-testing post-intervention, which was implemented in some of the reviewed studies, therefore also seems appropriate and may be recommended for prospective studies to determine whether longer-term effects of an intervention have been obtained. Furthermore, cognitive load theory proposes an overload of working memory capacity during performance anxiety, and current evidence states the essential role of working memory for visual skills that are crucial for athletic performance [85,86]. Therefore, another worthwhile aspect for future research and interventions may be examining the link between visual skills and performance anxiety.…”
Section: Discussionmentioning
confidence: 99%